Inclusive Educational Innovation and Entrepreneurship in Peru: An Analysis of the National Beca 18 Program in Technical Higher Institutes - Mendoza Porras, Jorge Carlos; Alzamora De Los Godos Urcia, Luis Alex; Calderón Saldaña, Jully Pahola; Valladolid Marcos, Fiorella Sthefany; Pineda Medina, Javier Alejandro; Molina Torres, José Gregorio; Merchor Alvarado, Luis Armando (LACCEI, 2025)
This case study explores the educational trajectories of beneficiaries of the Beca 18 program who initially enrolled at IES Avansys and later completed their technical higher education at Cibertec Institute following its institutional integration (2019–2020). The study analyzes enabling and limiting factors that shaped the program's capacity to deliver inclusive, high-quality, and equitable education. Using an exploratory qualitative methodology, the research highlights critical lessons in academic reinforcement, curriculum relevance, intercultural competencies, institutional accompaniment, and labor insertion. Findings show that although the public-private co-management model fosters innovation and adaptation, persistent gaps in academic support systems, digital infrastructure, and coordination mechanisms hinder effective implementation. Participants converge on the need to strengthen monitoring strategies, promote flexible and culturally responsive pedagogies, and reinforce institutional capacities to consolidate educational innovation with equity and sustainability. Furthermore, the study underscores the importance of addressing rural-urban disparities, ensuring universal accessibility, and promoting personalized mentoring strategies to support vulnerable students. These elements are crucial for bridging opportunity gaps and encouraging entrepreneurial potential among scholarship holders, thereby contributing to broader goals of social inclusion and development.